Design and Development of an Interactive Learning Media Based on Authoring Tools for Fundamental Competencies in Computer Networking and Telecommunications Education - Aristo , Muhar; Irfan, Dedy (Universitas Islam Negeri Raden Intan Lampung, 2026)
The rapid advancement of digital technology has intensified the demand for innovative learning systems capable of enhancing student engagement and supporting effective knowledge acquisition, particularly in vocational education. However, many existing digital learning tools remain fragmented, lacking integration between instructional content, interactivity, and assessment. This study aims to develop an integrated interactive learning system based on authoring tools for computer networking and telecommunications education. The research employed a Research and Development approach using the Multimedia Development Life Cycle model, encompassing concept, design, material collecting, assembly, testing, and distribution stages. The developed system integrates instructional materials with embedded formative assessment to support active learning and continuous feedback. Functional testing using black-box methods demonstrated a 100% success rate across all system components, indicating high technical reliability. Furthermore, expert validation involving material and media experts revealed that the system achieved a “very valid” classification, with an overall score of 90%, confirming its pedagogical and technical feasibility. The integration of interactive features such as quizzes and educational games significantly enhances cognitive engagement and supports deeper learning processes. This study contributes by proposing an integrated learning architecture that unifies content delivery, interactivity, and embedded assessment within a single platform. The findings highlight the potential of such systems to improve learning effectiveness in vocational education. Therefore, this study offers a scalable and impactful solution for advancing technology-enhanced learning environments in the digital era.